"تجربة جامعة السّلطان الشّريف علي الإسلاميّة في تعليم اللّغة العربيّة عن بعد "دراسة وصفيّة تحليليّة - صالح سبوعي; سيتي سارا بنت الحاج أحمد (AR-RĀ’IQ, 2021)
This paper presents the experience of one of the Islamic world universities in teaching Arabic language online (remotely); It is the Sultan Sharif Ali Islamic University (UNISSA). The paper dealt with this experience by stating its most important components, characteristics, reasons, and the most important challenges and difficulties it faced, at the same time, the study suggested some recommendations that may contribute to addressing those challenges. The study concluded that the experience of "Teaching Arabic language online" at Sultan Sharif Ali Islamic University is a very modern experience created by the circumstances of the Corona pandemic, which obligated everyone to social distancing as a part of safety measures as well as one of the foundations of distance education. The study concluded also that this experience has strengthened the idea of adopting this system in the future, and taking it as part of the education system at the university; taking into account the tremendous technological developments that have imposed themselves on the world and the changes in the life system with the pandemic and beyond it, especially in the Sultanate of Brunei Darussalam, which is considered a role model in controlling the pandemic and preventing its spread. The study recommended the need to conduct more field research to determine the appropriateness of this type of education for learners, and the extent to which it achieves its educational goals.